Support of Family For Type 2 Diabetes Mellitus Patients in Primary Health Center During The Covid-19 Pandemic - Citra Windani Mambang Sari; Dian Ratu Hilmi; Dadang Purnama (Journal of Nursing Science Update (JNSU), 2023)
Diabetes Mellitus is one chronic disease that is still a health problem requiring prolonged treatment, so good family support is needed. This research aims to identify family support for diabetes mellitus type II patients at the primary health centre. The research conducted is by using a quantitative approach. The sampling technique used was a total sampling as much of 91 respondents. The instrument used was a questionnaire, which included: demographic data and family support according to the Hensarling Diabetes Family Support Scale (HDFSS). Data analysis was carried out using descriptive analysis and was used frequency distribution and percentage. This research showed that family support for diabetes mellitus sufferers was mostly good, with a percentage of 91.2%, emotional support had good support (93.4%), reward support had good support (79.1%), and instrumental support had good support. (78.0%), information support has good support (93.4%). The research results are expected to provide information and knowledge related to family support applied to diabetes mellitus sufferers